2002
DOI: 10.5271/sjweh.690
|View full text |Cite
|
Sign up to set email alerts
|

Time control, catecholamines and back pain among young nurses

Abstract: Elfering A, Grebner S, Semmer NK, Gerber H. Time control, catecholamines and back pain among young nurses. Scand J Work Environ Health 2002;28(6):386-393.Objectives This study had two objectives. First, it addressed concern with the contribution of work stressors and resources to the development of back pain, over and above the influence of biomechanical work factors. Second, using recent models about the role of the sympathetic-adrenal medullar system in musculoskeletal problems as its basis, it tested whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 24 publications
1
47
0
2
Order By: Relevance
“…Furthermore, norepinephrine was associated with work stressors. This finding is in line with the results of previous studies that showed a similar association between work conditions, musculoskeletal pain, and norepinephrine excretion (3,10). Both sustained activation during work and lack of muscular relaxation after work may cause pain.…”
Section: Elfering Et Alsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, norepinephrine was associated with work stressors. This finding is in line with the results of previous studies that showed a similar association between work conditions, musculoskeletal pain, and norepinephrine excretion (3,10). Both sustained activation during work and lack of muscular relaxation after work may cause pain.…”
Section: Elfering Et Alsupporting
confidence: 93%
“…With respect to catecholamines, both epinephrine and norepinephrine should be related to musculoskeletal pain. However, norepinephrine is more proximally linked to muscle activity and musculoskeletal pain than epinephrine is (10). Altogether, evidence is increasing that chronic work-related stress, lack of rest, and recovery after work contribute to the development of persistent musculoskeletal pain (5).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have found that nursing is very strenuous work that causes a variety of pathological symptoms. For example, Elfering et al (2002) found that nurses in Switzerland are at risk for low-back pain; Lavanco (1997) found that in Sicily burnout is more prevalent among nurses than teachers, and Stordeur et al (2001) found that emotional exhaustion was the consequence of work-related stress factors among Belgian nurses. Occupational stress among nurses is associated with a variety of personal and institutional factors.…”
Section: Occupational Stress Among Icelandic Nursesmentioning
confidence: 99%
“…Numerous studies have shown that nursing is strenuous work and hence that occupational stress is prevalent among nurses (Elfering et al, 2002;Lavanco, 1997;Lee and Wang, 2002;Santos et al, 2003). A strong negative relation has been found between nurses' occupational stress and job satisfaction (Blegen, 1993), and it has also been reported that growing occupational stress results in increasing turnover rate and causes more and more nurses to leave the nursing profession (Shader et al, 2001).…”
mentioning
confidence: 99%